An analytical approach of elimination of ambipolarity of DPDG- TFET using strained type II staggered SiGeSn heterostructure. (May 2020) - Shaw, Namrata; Sen, Gopa; Mukhopadhyay, Bratati
Abstract : The effect of ambipolarity puts TFET in an unfavorable position and restricts its superiority. The inclusion of a drain pocket at the drain-channel junction can prove it to be a realistic and successful way to remove the ambipolarity completely. In this paper, a 2-D analytical model has been presented for a Drain Pocket Double Gate Tunnel Field Effect Transistor (DP DG-TFET). The theoretical model agrees well with the previously reported data of Si DP DG-TFET. In this work, the SiGeSn heterostructure is used to achieve a lower bandgap and therefore to improve the tunnelling probability. A high ON current without any ambipolarity can be achieved from such type of DP DG-TFET. Highlights: Strained Ge1-x-y Six Sny /Ge1-a-b Sia Snb based Drain Pocket (DP) Double Gate TFET. Ambipolarity is completely suppressed. Presence of heterojunction at the source-channel interface reduces tunnelling barrier. Higher ON current is achieved than the conventional Si based DG-TFET.